Formation of personality's acme-qualities as a component of physical education specialists' acmeological competence - T.Hr. Dereka (H.S. Skovoroda Kharkov National Pedagogical University, 2016)
Purpose: to determine characteristics of acme-qualities' formation in physical education specialists and determine correlations between components. Material: in the research students of "Physical education" specialty (n=194) participated. For assessment personality's qualities special tests were used. Organization abilities, communicative abilities, creative potential, demand in achievement, emotional information level, control of emotions and etc. were assessed. Results: we determined components of personality's acme-competence component in physical education specialists. We found density and orientation of correlation and influence of acme-qualities on personality's component. By the results of factorial analysis we grouped, classified components by four factors and created their visual picture. The accumulated percentage of the studied factors' dispersion was determined. Conclusions: continuous professional training of physical education specialists on acme-principles resulted in formation of personality's acme-qualities. They facilitate manifestation of personality's activity in the process of professional formation and constant self-perfection.